Avaliação da resistência à corrosão localizada do alumínio em juntas dissimilares al-ti soldadas por fricção por ponto (FSpW) - Vacchi, Guilherme dos Santos (Universidade Federal de São Carlos, 2017)
The work evaluated the effect of the FSpW welding process on the aluminum surface in two overlapping welded joints, AA6181-T4/Ti-6Al-4V and AA5754-H22/Ti-6Al-4V. The microstructural changes were evaluated through optical microscopy (OM), scanning electron microscopy (SEM) and the mechanical properties were evaluated through Vickers microhardness mapping. The localized corrosion resistance as a function of the welding process was assessed through potentiodynamic polarization tests in a 0.01 M NaCl solution and 0.1 M sodium sulfate (Na2SO4). Additionally, immersion tests in NaCl and H2O2 solution (AA6181-T4) and nitric acid (70%) (AA5754-H22) were conducted to evaluate the resistance to intergranular corrosion. Optical microscopy revealed a recrystallization and recovery process in the heat-affected zone (HAZ) region for the AA5754-H22 alloy and a slight increase in grain size in this region for the AA6181-T4 alloy, resulting from the thermal cycle generated by the welding process. It was possible to observe the occurrence of the dynamic recrystallization process inside both alloys stir zone (SZ) due to the high temperature deformation of FSpW welding. Scanning electron microscopy analysis shows the presence of Al (Fe, Mn, Mg, Si) and Mg2Si precipitates in both alloys, and that the welding process stimulates a breakdown of these precipitates in the SZ. Potentiodynamic polarization analysis show that the corrosion potential (Ecorr) for all welding regions are similar. However, the SZ has nobler pitting potential (Epit) for both alloys. Immersion tests do not reveal the presence of intergranular corrosion in any welded region of the AA5754-H22 alloy, whereas for the AA6181-T4 alloy, presence of a slight corrosive attack on the surface of all welding regions was noted.
Keywords: FSpW; Dureza; Soldagem por fricção por ponto; Corrosão por pites; Juntas dissimilares; Ligas de alumínio; Friction spot welding; FSpW; Dissimilar joint; Aluminum alloys; Hardness; Pitting corrosion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO